2015
DOI: 10.2146/sp150027
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated heparin anticoagulation using estimated blood volume based dosing versus weight-based dosing in a Veteran population

Abstract: EBV dosing achieved quick therapeutic anticoagulation with less bleeding compared to WB dosing in a veteran population. Due to the study's limitations, larger, randomized, comparative trials are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Clinical utility has been suggested with this strategy in a previous study assessing therapeutic anticoagulation with UFH. 2 We sought to describe the relationship between EBV, daily UFH dose, and the incidence of VTE and bleeding in underweight (≤50 kg or BMI ≤18.5 kg/m 2 ), critically ill patients.…”
mentioning
confidence: 99%
“…Clinical utility has been suggested with this strategy in a previous study assessing therapeutic anticoagulation with UFH. 2 We sought to describe the relationship between EBV, daily UFH dose, and the incidence of VTE and bleeding in underweight (≤50 kg or BMI ≤18.5 kg/m 2 ), critically ill patients.…”
mentioning
confidence: 99%
“…36 A small study of 32 patients who received unfractionated heparin infusions showed that EBV-based dosing was associated with a nonsignificant decrease in time to therapeutic range as well as an increase in the percentage of patients with first anti-Xa level within therapeutic range compared to weight-based dosing. 37 In a recent study in trauma patients, EBV (rho = 0.57) had a higher correlation with anti-Xa levels compared to BMI (rho = 0.20) and TBW (rho = 0.46). 23 Dose-per-unit EBV (aOR 2.54) and dose-per-unit TBW (aOR 1.89)…”
Section: Discussionmentioning
confidence: 89%
“…Since all heparins remain primarily in the intravascular space after intravenous administration or subcutaneous absorption, it is logical that EBV may be the best predictor of dose needed 36 . A small study of 32 patients who received unfractionated heparin infusions showed that EBV‐based dosing was associated with a nonsignificant decrease in time to therapeutic range as well as an increase in the percentage of patients with first anti‐Xa level within therapeutic range compared to weight‐based dosing 37 . In a recent study in trauma patients, EBV (rho = 0.57) had a higher correlation with anti‐Xa levels compared to BMI (rho = 0.20) and TBW (rho = 0.46) 23 .…”
Section: Discussionmentioning
confidence: 99%